Sophie Christine und Carl Heinrich Laeisz. Eine biographische Annäherung an die Zeiten und Themen ihres Lebens - Gerhardt, Johannes (Mäzene für Wissenschaft, 2007)
With the renaming of the Music hall (Musikhalle) Hamburg in "Laeiszhalle" in January 2005, a name in the Hanseatic city has been brought back to the forefront. The volume traces the fascinating life of Sophie and Carl Laeisz. Both have distinguished themselves as patrons not only at the foundation of this concert hall, but also as donors of the Hamburgische Wissenschaftliche Stiftung. Her life reflects the central tendencies of Hamburg's 19th century history: civic commitment and the Hanseatic city's place in the world economy.